A blockchain‐based approach to secure electronic health records using fuzzy commitment scheme. Issue 4 (5th April 2022) - Barman, Subhas; Chattopadhyay, Samiran; Samanta, Debasis; Barman, Sayantani
Abstract: The electronic health record is the most sensitive data which needs a secure framework to protect it from data breaching. Recently, blockchain‐based platforms are used in healthcare services for data security, data sharing and availability of immutable data during medico‐legal verification. In this paper, a blockchain‐based approach for securing electronic health records using elliptic curve cryptography (ECC) and a biometric‐based fuzzy commitment scheme is proposed. The proposed approach addresses common issues of blockchain, namely scalability, integrity, confidentiality and decentralization of the ledger. The security of the proposed scheme was verified using the Random Oracle model. The block time for a variable number of transactions per block was measured and compared with the block time of the existing approaches. Also, the proposed approach was compared with the existing approaches with reference to various security features.